Prognostic value of culprit artery double-stranded DNA in ST-segment elevated myocardial infarction - Wang, Xiqiang (Sci Rep, 2018)
The double-stranded DNA (dsDNA) which is scaffold of neutrophil extracellular traps (NETs) has been reported to be associated with the occurrence of major adverse cardiovascular events (MACEs) in patients with coronary atherosclerosis. However, the relationship between the dsDNA and the occurrence of MACEs in patients with ST-segment elevated myocardial infarction (STEMI) remains unclear. In this study, 142 consecutive STEMI patients were admitted to medical institutions. Blood from the infarct-related coronary artery (ICA) and peripheral artery (PA) were obtained during percutaneous coronary intervention. Clinical follow-up was performed to analyze the occurrence of MACEs. Patients were divided into low ds-DNA group and high dsDNA group according to the cut-off value of ICA dsDNA. Mean follow-up time was 24.52 months in low dsDNA group and 25.71 months in high dsDNA group. dsDNA in the ICA was significantly higher than in the PA (p = 0.038) and Spearman's correlation analysis showed that they were positively correlated (r = 0.758; p < 0.01). ICA dsDNA correlated negatively with ST-segment resolution (r = −0.227; p = 0.007). The long-term MACEs rate was higher in high dsDNA group than low dsDNA group (23.7 vs. 6.7%, p = 0.015). The ICA dsDNA (OR 7.43 95% CI 1.25 to 4.07, p = 0.027), Killip class (OR 5.01 95% CI 1.11 to 4.37, p = 0.025), BMI (OR 1.36 95% CI 1.06 to 1.7, p = 0.016) and white blood cell count (OR 1.27 95% CI 1.03 to 1.57, p = 0.024) were independent predictors of the occurrence of MACEs.